Quantifying the non-breeding provenance of staging Ruffs, Philomachus pugnax , using stable isotope analysis of different tissues - Schmaltz, L.E.; Jelle Loonstra, A.H.; Wymenga, E.; Hobson, K.A.; Piersma, T. (Journal of Ornithology, 2018)
International conservation efforts for migratory populations are most effectively based on quantification of the geographical linkages between wintering, staging, and breeding areas, patterns that may not remain constant in times of global change. We used stable isotope (δ 13C, δ 15N, and δ 2H) measurements of different tissues representing distinct periods of dietary integration to quantify the non-breeding provenance of a threatened staging population of Ruffs Philomachus pugnax. In 199 staging Ruffs captured in 2012 during northward migration in the Netherlands, we compared the multi-isotope patterns of feathers grown at wintering grounds, with the δ 13C and δ 15N profiles of blood cells and plasma representative of staging areas. Few birds had the 13C-depleted and 15N-enriched feathers suggestive of wintering quarters in European agricultural areas. Most Ruffs had higher feather δ 13C values, suggesting that they wintered in sub-Saharan Africa. Feather δ 2H values were not informative due to the overlap of values from European and African moulting sites. Blood cell δ 13C and δ 15N values indicated that sub-Saharan Ruffs fuelled on low trophic-level foods in habitats dominated by C3 terrestrial or freshwater aquatic primary production, e.g. the rice fields in Africa or the Mediterranean. Stable isotope ratios in plasma suggested that Ruffs made stopovers in southern European agricultural areas. Stable isotopes thus enabled assessments of wintering origin in large numbers of birds. We further propose that conservation measures to protect Ruffs must include the adequate management of sub-Saharan wetlands, based on a better understanding of the role of human-made rice fields for fuelling birds.